E-MODUL DEVELOPMENT FOR SPREADSHEET SUBJECTS - Fajjahdiyanti, Fara Eldina; Laily, Nujmatul (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2024)
The aim of this research is to produce an interactive e-modules for spreadsheet subjects. This research uses a research and development approach by adopting the Borg and Gall development model. The research subjects were students of class X Accounting and Finance. The results show that the flipbook-based interactive e-module is very good to use, with validation test results for media experts at 81.3%, material experts at 88%, and students at 82.8%. Apart from that, there is a significant difference in the use of interactive e-modules, as seen by an increase in the total mean score of the posttest which is higher than the pretest. Therefore, the existence of a flipbook-based e-module as a learning media is very effective and suitable for use in supporting the spreadsheet learning process.